Simplify the following expression, and rewrite it in an equivalent form with positive exponents.

-14xy / 42x^5y^8

6 answers

-14xy/42x^5y^8
=-1/3 x^(1-5) y^(1-8)
=-1/3 x^-4 y^-7
=-1/[3(x^4y^7)]
-14xy/42x^5y^8

42=3*14

-14/42= -14/(3*14)= -1/3

-14xy/42x^5y^8 =

-xy/3x^5y^8

Multiply with x^5*y^8

-xy/3x^5y^8= -x*y*x^5*y^8/3=
-x^6*y^9/3

-14xy/42x^5y^=-xy/3x^5y^8=-x^6*y^9/3
alx answer is wrong
-14xy/42x^5y^8= -xy/3x^5y^8= -x^6*y^9/3
"-14xy/42x^5y^8= -xy/3x^5y^8= -x^6*y^9/3"

please check your answer.
please help me with the factorization,findin the middle term